Investigating the role of autophagy in regulating innate cytokine response of human lung epithelial cells to respiratory syncytial virus - Azman, Nur Amiera Fatin (2021)
Human respiratory syncytial virus (RSV) is one of the leading causes of childhood acute lower respiratory tract infection in Malaysia. It is responsible for significant morbidity and mortality among children, the elderly and individuals with chronic respiratory illnesses worldwide. Despite years of effort, currently there are neither licensed vaccines nor specific antiviral drugs against RSV. The severity of RSV-acquired diseases is predominantly caused by an overexuberant inflammatory response to the virus. Thus, a complete understanding of all the mechanisms that regulate cytokine production during RSV infection is crucial to further refine the therapeutic strategies to alleviate the excessive RSV-induced inflammatory response. Autophagy has recently been linked to the regulation of host cytokine responses to several viruses, including the vesicular stomatitis virus and the human immunodeficiency virus. In vivo studies using mouse model have shown that inhibiting autophagy attenuates the production of RSV-induced cytokines. However, the involvement of autophagy in the innate cytokine response of RSV-infected human cells has not been reported. Lung epithelial cells are known to be the main site of RSV infection and replication. Therefore, the main aim of this study was to determine the potential role of autophagy in regulating the production of RSVinduced innate cytokine C-X-C motif ligand 8 (CXCL8) and C-C motif ligand 5 (CCL5) production in lung epithelial BEAS-2B cells using both pharmacological inhibitors and short-interfering RNA knockdown approaches. It was found that RSV infection induced autophagy in BEAS-2B cells, as measured by CytoID® Autophagy Kit-based fluorescence microscopy and flow cytometry analyses. Inhibition of autophagy was performed using both pharmacological inhibitors and short-interfering RNA knockdown approaches. To confirm that autophagy inhibition does not affect cell viability, lactate dehydrogenase (LDH) assay was conducted. It was observed that inhibition of autophagy by the pharmacological inhibitors SAR405 and chloroquine (CQ); and siRNA-mediated knockdown of the autophagy protein Beclin-1 (Bec-1) did not kill the BEAS-2B cells. Human respiratory syncytial virus (RSV) is one of the leading causes of childhood acute lower respiratory tract infection in Malaysia. It is responsible for significant morbidity and mortality among children, the elderly and individuals with chronic respiratory illnesses worldwide. Despite years of effort, currently there are neither licensed vaccines nor specific antiviral drugs against RSV. The severity of RSV-acquired diseases is predominantly caused by an overexuberant inflammatory response to the virus. Thus, a complete understanding of all the mechanisms that regulate cytokine production during RSV infection is crucial to further refine the therapeutic strategies to alleviate the excessive RSV-induced inflammatory response. Autophagy has recently been linked to the regulation of host cytokine responses to several viruses, including the vesicular stomatitis virus and the human immunodeficiency virus. In vivo studies using mouse model have shown that inhibiting autophagy attenuates the production of RSV-induced cytokines. However, the involvement of autophagy in the innate cytokine response of RSV-infected human cells has not been reported. Lung epithelial cells are known to be the main site of RSV infection and replication. Therefore, the main aim of this study was to determine the potential role of autophagy in regulating the production of RSVinduced innate cytokine C-X-C motif ligand 8 (CXCL8) and C-C motif ligand 5 (CCL5) production in lung epithelial BEAS-2B cells using both pharmacological inhibitors and short-interfering RNA knockdown approaches. It was found that RSV infection induced autophagy in BEAS-2B cells, as measured by CytoID® Autophagy Kit-based fluorescence microscopy and flow cytometry analyses. Inhibition of autophagy was performed using both pharmacological inhibitors and short-interfering RNA knockdown approaches. To confirm that autophagy inhibition does not affect cell viability, lactate dehydrogenase (LDH) assay was conducted. It was observed that inhibition of autophagy by the pharmacological inhibitors SAR405 and chloroquine (CQ); and siRNA-mediated knockdown of the autophagy protein Beclin-1 (Bec-1) did not kill the BEAS-2B cells.